Scientific mapping of digitalization in architectural education for sustainability - Zeynep Kamile Cenk; Semra Arslan Selçuk (Vitruvio: International Journal of Architectural Technology and Sustainability, 2025)
In today’s world, where digital technologies are being used more and more every day, architectural education is one of the fields experiencing radical changes. Although many studies in the literature investigate digitalization in architectural education or sustainable architectural education, there are few studies on the digitalization of architectural education to ensure sustainability. This research aims to identify the scientific production on digitalization in education for a sustainable architecture indexed in the international databases Scopus and Web of Science and to determine the maturity of the research on this subject. The results consist of 100 articles published between 2007 and 2024. The data obtained in the study were visualized and analysed with Biblioshiny, VOSviewer, and SankeyMatic programs. The articles obtained were categorized and evaluated to determine which keywords indicated which research topics. In the study results, various research areas such as BIM, simulation, digital fabrication, AR-VR technology, and artificial intelligence from digital technologies have been prominent topics in recent years. The results of this review emphasize the need for more research on the subject and the importance of multidisciplinary studies.